Development of parallel and fan-shaped beam mixed-projection optical tomography - Siti Zarina, Mohd. Muji, Dr.; Ruzairi, Abdul Rahim, Prof. Dr.; Mohd Hafiz, Fazalul Rahiman; Yusry, Yunus; Zulkarnay, Zakaria; Nor Muzakkir, Nor Ayub (International Frequency Sensor Association Publishing (IFSA), 2013)
Link to publisher's homepage at http://www.sensorsportal.com